CRISPR-based, genotype-specific detection of yellow head virus genotype 1 with fluorescent, lateral flow and DNAzyme-assisted colorimetric readouts - Aiamsa-at P. (2023)
The yellow head virus complex comprises 8 genotypes of single-stranded RNA viruses infecting penaeid shrimp, but only yellow head virus genotype 1 (YHV1) is capable of causing massive shrimp mortalities and severe economic losses. However, current molecular techniques could not detect YHV1 with high specificity, or require complicated protocols for this purpose. Here, we developed a combination of reverse-transcriptase recombinase polymerase amplification (RT-RPA) and CRISPR-Cas detection (“RR-Cas”) for the genotype-specific detection of YHV1. The method can be completed within 1.5 h at a constant temperature near 37 °C, after which the results can be visualized by the naked eye using fluorescent, lateral flow, and G-quadruplex DNAzyme-assisted colorimetric assays. The detection limit is 100 copies of plasmid DNA and 100 fg of total RNA from YHV1 infected shrimp, comparable to the WOAH-recommended one-step RT-PCR protocol. In the evaluation of clinical samples, RR-Cas was found to be less sensitive than nested RT-PCR, but displayed superior specificity, yielding no false positive results towards samples containing YHV2 and 3. Overall, our findings suggest that RR-Cas is a powerful addition to the toolkit for genotype-specific viral diagnosis in shrimp aquaculture, with the potential to greatly streamline disease surveillance and management in the shrimp industry.